Mapping the main food safety governance actors at the time of the 2017/18 Listeria outbreak in South Africa for improved lessons in governance. - Adelle, Camilla (University of Pretoria, 2022)
Mini Dissertation (MA (Political Sciences))--University of Pretoria, 2021.